Determination of Total Arsenic of some Food and Cash Crops, Vegetation, Cooked Food, Fish, Meat, Soil and Water from Kumasi, Obuasi and their Environs (Journal of Science and Technology, 2016)
The total arsenic of some Ghana food and cash crops, vegetation, cooked food obtained from some horues, locll fish, and meal, as well as some soil and water samples from Kumasi and Obuasi were deter-mined. In all, 266 samples were examined. Sampling depended on which samples were available and obtain-able at the different locations. Vegetation was as possible collected from sources of water utilize for domestic purposes. Absorption Spectrophotometry was employed. Arsenic concentration values for Kumasi ranged between 0.07 and 7.20 mg/kg whilst.in Obuasi a range of 0.12 to 70.50 mg/kg was obtained. The data showed that arsenic levels for Obuasi Samples were much higher than those from Kumasi.